Narration or Story as an Instrument or Knot of (De)humanization or ... - GAJIN, Igor (Anafora, 2023)
In science and humanistic teaching, the precedence of quantification, measurability, bureaucratic content organization, and neopositivism – neo in terms of statistical data processing – is increasingly visible. It evidently follows the logic of a computerized presentation of information (instead of knowledge), and thus the capitalist disciplining and controlling of Gorz’s “intangible labor.” With the Internet, network philosophy, hyper- text, and hyperinformation overload, a fragmented, dispersed, and decontextualized digital culture invokes in both theory and practice an oppositional reaction towards reaffirming the classic story or storytelling as an archetypal form of humanizing, organizing, and conceiving human experience and knowledge. However, when Amazon announces that the author will be paid an amount corresponding to the amount of pages of his text that are read through apps for tracking such results, when Christian Salmon discovers storytelling as a new instrument of corporate business, when storytelling becomes an imperative of commercial literature and a means of industrialized standardization of literature, all facilitated by the trend of creative writing workshops, the question is to whom and to what purpose the story serves today. Was the last century’s (post)modernist deconstruction of the text and the disintegration of its ideologized meaning not as humane as it was unreadable, as opposed to today’s seduction of the consumerist object through fabrications from the pen of “content providers”?